PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI TUTOR SEBAYA PADA PEMBELAJARAN MENGGAMBAR BENTUK - VELLA LINTANTIA NOBER, Drs. Abd. Hafiz, M.Pd, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2015)
This research was designed for revealing the difference betweenlearning achievement of the students taught by using peer tutor strategyand those taught by using conventional strategy in the learning process ofshapes in class X DPIL of SMK Negeri 4 Padang. The data gotten wasanalyzed throught descriptive analysis and inductive analysis. Based onthe result of hypothesis test it was figured out that the value of tcalculated(3.60) was bigger than ttable (2.00). this result signified that Ho was rejected and H1 was accepted indicating that there was a significant difference between learning achievement of the students taught by using peer tutor strategy and those taught by using conventional strategy in the learning process of shapes in class X DPIL of SMK Negeri 4 Padang.Kata kunci: hasil belajar, mata pelajaran menggambar bentuk, strategitutor sebaya